2005
DOI: 10.1089/aid.2005.21.152
|View full text |Cite
|
Sign up to set email alerts
|

Subtype B and Subtype C HIV Type 1 Recombinants in the Northeastern State of Manipur, India

Abstract: The predominant HIV-1 strain circulating in India is subtype C. However, subtype A and B strains of HIV-1 have also been reported in India. In 1999, the first A/C recombinant strain was reported from Pune in India. Intravenous drug users (IVDUs) from the northeastern region of India have a high HIV-1 seroprevalence. Studies carried out in intravenous drug users in the northeastern region of India have shown that HIV-1 subtype C is the predominant strain infecting IVDUs. Fourteen blood samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The presence of multiple subtypes circulating in Manipur suggests the likelihood of recombinant viruses evolving in this region. Indeed, this has been corroborated by a recent study which reported presence of B/C recombinants from this region [26]. Apart from north-eastern states there are also sporadic reports of the presence of A/C and B/C recombinants from West and South India [12,22].…”
Section: The Indian Scenariosupporting
confidence: 55%
“…The presence of multiple subtypes circulating in Manipur suggests the likelihood of recombinant viruses evolving in this region. Indeed, this has been corroborated by a recent study which reported presence of B/C recombinants from this region [26]. Apart from north-eastern states there are also sporadic reports of the presence of A/C and B/C recombinants from West and South India [12,22].…”
Section: The Indian Scenariosupporting
confidence: 55%
“…The predominant circulating strain, both in Mumbai in the West [57] and in Chennai in the South [58], is subtype C. In Manipur, near China and Myanmar, four of 14 specimens were B/C recombinants [59].…”
Section: Asia and The Pacificmentioning
confidence: 99%
“…Furthermore, baseline CD4 cell counts and HIV-1 RNA levels have been shown to predict immunologic and virologic responses in HIV infected Since the predominant subtype found circulating in India is HIV-1 subtype C (Bhanja et al, 2005;Halani et al, 2001;Mandal et al, 2000;Sahni et al, 2002;Siddappa et al, 2004;Tripathy et al, 2005), these assays may not be best suited for India. Hence, we thought it would be appropriate to develop a real time PCR assay for quantification of viral loads in HIV-1 infected patients from South India.…”
Section: Introductionmentioning
confidence: 99%